Consulting report - Municipality of Surco: social project proposal to reduce childhood obesity of primary education students in a public school in the District of Santiago de Surco - Flores Merino, Romina (2024)
This thesis addresses the increasing prevalence of childhood obesity and overweight in the district of Santiago de Surco, Lima, Peru, with a focus on primary school children aged 6 to 11 years. By using the Design Thinking Methodology, the study analyzes the key factors contributing to this public health issue, such as limited access to nutritious food and insufficient physical activity. The thesis presents a proposed solution through a social program that provide free after-school physical activities, in partnership with the Municipality of Santiago de Surco and Smart Fit. Its goal is to increase the number of hours of exercise that children participate in on a weekly basis, thereby addressing on of the main contributors of the childhood obesity. The study also evaluates the scalability of the program, considering its potential expansion to other age groups, schools, and districts. Additionally, the program emphasizes the importance of the community collaboration, including the parents and local businesses, to ensure the active participation and the initiative’s financial sustainability. By promoting an active lifestyle and health habits of children, the thesis contributes to combat childhood obesity in Peru, aligning with the country’s Sustainable Development Goals 2 and 3.